MAINTAINING ESSENTIAL VETERINARY SERVICES IN A PUBLIC ONE HEALTH CLINIC DURING A PANDEMIC & MAINTAINING ESSENTIAL ANIMAL SHELTERING SERVICES DURING A PANDEMIC - Orchard, Ronald (My University, 2021)
The COVID-19 pandemic forced society to appreciate the truly essential services; these range from healthcare or fire departments to food service and primary schools. Another public benefit not traditionally thought of as an essential service is animal sheltering, and the pandemic proved this by forcing animal shelters to figure out how to maintain their programming while providing for the safety of the animals, potential pet-adopters, volunteers and staff. The goal of this project was to aid these organizations by compiling the current best practices from animal sheltering organizations and public health institutions, reconciling these protocols with the rapidly developing knowledge base about the COVID-19 disease, and developing recommendations on best practices and protocols for the Prairie Paws Animal Shelter in Ottawa, KS. These practices focused on two aspects: safety conscious operating protocols and minimizing the amount of clients in the shelter at a time. An explanation of these practices was presented to shelter stakeholders and staff, allowing for a successful rollout. These protocols, while specifically created for this shelter organization, can be used as a starting point for any animal welfare organization navigating the resumption of programming during an infectious disease outbreak.
Keywords: Covid-19; One Health; low-income; animal shelter; public clinic; veterinary